Comparative characteristics of mesenchymal stem cells derived from reamer-irrigator-aspirator, iliac crest bone marrow, and adipose tissue - Toosi, S; Naderi-Meshkin, H; Kalalinia, F; Peivandi, M T; Hossein Khani, H; Bahrami, A R; Heirani-Tabasi, A; Mirahmadi, M; Behravan, J (Cellular and Molecular Biology, 2016)
Mesenchymal stem cells (MSCs) have been considered promising tools for new clinical concepts in supporting cellular therapy and regenerative medicine. More recently, Ream/Irrigator/Aspirator (RIA) was introduced as a source of MSCs. In this study we compared MSCs derived from three different sources (iliac crest bone marrow (ICBM), adipose tissue (AT), and (RIA)) regarding the morphology, the success rate of isolating MSCs, colony frequency, expansion potential, osteogenic and chondrogenic differentiation capacity. MSCs were isolated from three different sources and flow cytometric analyses were performed for cell characterization. Colony-forming unit-fibroblast (CFU-F) assay and population doubling time (PDT) were evaluated for MSCs derived from three different sources and differentiation potential of RIA, ICBM-, and AT-MSCs were determined by staining. Additionally, gene expression profiles for tissue specific markers corresponding to osteogenesis and chondrogenesis were analyzed using real time polymerase chain reaction (RT-PCR). Cultured with the appropriate condition, osteogenic and chondrogenic differentiation could be confirmed in all MSC preparations. Flow cytometry analysis indicated that RIA- and AT-derived MSCs have more homogenous populations than ICBM-MSCs. A comparison of the colonogenic ability in different tissues by CFU-F assay after 10 days showed that more colonies are formed from RIA-MSCs than from ICBM-MSCs, and AT-MSCs. AT-MSCs, were dispersed with no obvious colonies. The RIA-MSCs underwent osteogenesis and chondrogenesis at a faster rate than ICBM and AT-MSCs. Direct comparisons of RIA- to ICBM- and AT-MSCs have shown the RIA-MSCs have higher differentiation toward osteoblast and chondrocytes compared to other sources of MSCs. Hence, RIA-MSCs may be recommended as a more suitable source for treating orthopedic disorders.